VO2max and arterial O2 saturation at sea level and 610 m - Gore, C. J.; Hahn, A. G.; Watson, D. B.; Norton, K. I.; Campbell, D. P.; Scroop, G. S.; Emonson, D. L.; Wood, R. J.; Ly, S. V.; Bellenger, S. J.; Lawton, (Medicine & Science in Sports & Exercise, 1995)
The hypothesis that the VO2max of elite athletes, but not non-elite athletes, is decreased at sea-level compared with 610 m as a result of lower arterial oxygen saturation was tested. Neither value was significantly different between the two altitudes for the non-elite group, but were for the elites. Implication: Trained elite athletes are more sensitive to minor changes in altitude and lower altitudes than non-elite athletes.